Pig manure in the production of banana seedlings - Torsian, Waleska Silva; Almeida, Leandro da Silva; Silva, Nara Cristina de Lima; Nascimento, Marcely Ferreira; Caron, Vanessa Cristina (Revista Agrogeoambiental, 2020)
Pig breeding generates waste that, if not handled correctly, can cause serious environmental problems. The application of these residues in the soil appears as a sustainable alternative, since the manure, being rich in organic matter and mineral nutrients, promotes the improvement of the physical, chemical and biological quality of the soil avoiding the contamination of natural resources if it is released in the water or directly on the ground without proper treatment. The objective of this study was to evaluate the development of banana seedlings fertigated with pig slurry (PS) analyzing its efficiency compared to conventional treatment (chemical). The experiment was carried out in a completely randomized design with six treatments and six replications (3 seedlings per repetition), the doses being defined based on the fertilizer recommendation for the production of banana seedlings and the nutrient in greater concentration in the manure, which, in this case, was nitrogen, considered as the dose limiter. The results showed that PS was efficient in supplying nutrients to the banana seedlings and it can be used as a substitute for chemical fertilizer. The treatment with manure corresponding to 25.0% of the nitrogen recommended to produce banana seedlings provided the greatest development.